Gender and Geographic Predictors of Cyberbullying Victimization, Perpetration, and Coping Modalities Among Youth. (March 2019) - Ronis, Scott; Slaunwhite, Amanda
Cyberbullying has become an important public health issue due to documented associations among victimization, perpetration, and greater likelihood of depression, substance abuse, anxiety, insomnia, and school-related problems for adolescents. Less is known, however, about how youth cope with cyberbullying and the types of services and supports they are likely to use based on relevant socioeconomic, demographic and geographic factors. The objective of this project was to determine whether gender and geography, in combination with mental health and socioeconomic status, predicted cyberbullying victimization, perpetration, and patterns of coping and help seeking in a sample of youth aged 16 to 19 years ( N = 289). An anonymous online survey was used to gather information on cyberbullying victimization, perpetration, and methods for coping from youth from New Brunswick, Canada. The results of this study suggest that the likelihood of becoming a cyberbullying victim or perpetrator, as well as the coping modalities used to respond to bullying, are highly gendered and intersect with existing social and health inequities. Interventions aimed at bolstering resiliency should be developed in the context of the urban and rural school environments where coping skills are developed and refined.